Implementasi Program Desa Anti Korupsi Di Desa Pakatto Kecamatan Bontomarannu Kabupaten Gowa - Dewi Andini; Abdi Abdi; Nurwahid Nurwahid (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
: The purpose of this research is to find out how the implementation and obstacles of the anti-corruption village program in Pakatto Village, Bontomarannu District, Gowa Regency. The theory used in this study is the program implementation theory according to Charles O. Jones which mentions three basic activities, namely organization, interpretation, and application. The research method used is qualitative descriptive. The results of the study show that the implementation of the anti-corruption village program in Pakatto village initiated by the Corruption Eradication Commission in its implementation has been good. Judging from the structural organization and integrity of human resources, it has run optimally. From the aspect of interpretation, the program implementers have understood the goals and guidelines of the village program. In the implementation aspect, it was found that the realization of the implementation of the village work program went smoothly by holding a coffee morning activity with a Focus Group Discussion scheme and the existence of an Independent Digital Platform connected to the Website. Keywords: Implementation, Program, Anti-Corruption Village